THE PECULIARITY OF NEURO-DIDACTIC CONTENT AIMED AT DEVELOPING THE INTELLIGENCE OF PRIMARY SCHOOL STUDENTS - STAMBEKOVA, A.; Жұмабаева, Жәзира; NURZHANOVA, S. (Pedagogy and Psychology, 2025)
The article describes the specifics of neurodidactic content aimed at developing the intelligence of primary school students. The theoretical foundations of neurodidactics, including the concepts of neuroplasticity and cognitive development, are considered. The neuro-didactic content aimed at developing the intelligence of younger schoolchildren is analyzed. The meaning of the concept of neuro-didactic content is revealed, its definition is given, and its effectiveness and capabilities are revealed. A survey was conducted to determine the knowledge of primary school teachers about neurophysiological features, the development of the intelligence of primary school students, neurodidactic content, to determine what work they do in the development of the intelligence of their students, and to clarify the content of neurodidactic content and determine the possibility of neurodidactic content in the development of students ' intelligence. The results were verified using a coefficient scale and displayed in the form of a diagram and a table. According to the results of the survey, the educational level of primary school teachers in the field of intelligence development with the help of neurodidactic content was determined, as well as the content of neurodidactic content for the development of intelligence of younger schoolchildren was determined.